2014
DOI: 10.1111/ipd.12143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a school‐based oral health education programme on use of recommended oral self‐care for reducing the risk of caries by children in Nigeria

Abstract: This long term school based educational programme was able to increase school children's use of fluoride-containing toothpaste and twice daily tooth brushing, which are critical tools for reducing the risk of caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 16 publications
5
35
0
4
Order By: Relevance
“…These findings are comparable to those of previous studies [Petersen et al, 2004;Tai et al, 2009;Amalia et al, 2012;Esan et al, 2015] showing the effectiveness of educational programmes on children's toothbrushing behaviour. Tai et al [2009] reported that biweekly oral health education during a 3-year programme successfully increased the percentage of children brushing twice a day.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are comparable to those of previous studies [Petersen et al, 2004;Tai et al, 2009;Amalia et al, 2012;Esan et al, 2015] showing the effectiveness of educational programmes on children's toothbrushing behaviour. Tai et al [2009] reported that biweekly oral health education during a 3-year programme successfully increased the percentage of children brushing twice a day.…”
Section: Discussionsupporting
confidence: 89%
“…Schools were encouraged to have a policy regarding their children's oral health and to subsequently establish oral health-related activities or environments in schools. Studies on oral health-promoting schools were conducted in many countries, such as Indonesia, Taiwan, China, New Zealand, Nigeria, Finland, and Thailand [Petersen et al, 2001[Petersen et al, , 2004[Petersen et al, , 2015Tai et al, 2009;Anttonen et al, 2011;Amalia et al, 2012;Esan et al, 2015;Lai et al, 2016;Thornley et al, 2017]. Examples of the oral health supportive activities or environments established in schools were oral health education taught by professionals, oral health education integrated into the school curriculum and taught by school teachers, simple oral examinations conducted by teachers, toothbrushing after lunch, free toothbrushes and toothpaste (toothbrushing materials) for children, restricting sugary and junk food in schools, and providing vegetables and fruit in school meals [Kwan et al, 2005].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schools possess several inherent qualities that make them suitable for the presentation of oral health information. [2627282930313233]…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies conducted in Nigeria equally corroborate this finding [19, 38]. While the oral hygiene status has been shown to be an important correlate for caries occurrence, no study conducted in Nigeria till date has been able to demonstrate a relationship between frequency of tooth brushing and caries prevalence [3840].…”
Section: Discussionmentioning
confidence: 72%